Tunable attenuation in photonic liquid crystal fibers - Tefelska, Marzena Maria; Chychłowski, Miłosz S; Woliński, Tomasz R; Dąbrowski, Roman; Wójcik, Jan (Photonics Letters of Poland, 2009)
This paper presents initial experimental results on the influence of temperature on propagation properties of a new photonic crystal fiber filled with a novel low-birefringence NLC 1800B. The results obtained suggest great potential of the LC-filled photonic crystal fibers for fiber attenuators or modulators.